Degradation kinetics of peroxidase enzyme, phenolic content, and physical and sensorial characteristics in broccoli (brassica oleracea L. ssp. Italica) during blanching - Gonçalves, Elsa M. (2010)
The effects of water blanching treatment on peroxidase inactivation, total phenolic content, color parameters [-a*/b* and hue (h *)], texture (maximum shear force), and sensory attributes (color and texture, evaluated by a trained panel) of broccoli (Brassica oleracea L. ssp. Italica) were studied at five temperatures (70, 75, 80, 85, and 90 C). Experimental results showed that all studied broccoli quality parameters suffered significative changes due to blanching treatments. The vegetal total phenolic content showed a marked decline. Degradation on objective color and texture measurements and alterations in sensorial attributes were detected. Correlations between sensory and instrumental measurements have been found. Under the conditions 70 C and 6.5 min or 90 C and 0.4 min, 90% of the initial peroxidase activity was reduced. At these conditions, no significant alterations were detected by panelists, and a small amount of phenolic content was lost (ca. 16 and 10%, respectively). The peroxidase inactivation and phenolic content degradation were found to follow first-order reaction models. The zero-order reaction model showed a good fit to the broccoli color (-a*/b* and h *), texture, and sensory parameters changes. The temperature effect was welldescribed by the Arrhenius law.